Tinjauan Hukum Positif atas Kedudukan Negara sebagai Pemegang PNBP dalam Proses Kepailitan di Indonesia: (Studi Kasus Putusan Nomor 18/Pdt.Sus-Renvoi/2023/PN Niaga Medan) - Nicholas Napitupulu; Sudaryat; Aam Suryamah (CV Rewang Rencang, 2025)
State Receivables is one type of state revenue that must be paid to the Central Government. One form of State Receivables is Non-Tax State Revenue (PNBP). In the bankruptcy process, the State represented by the Ministry / Institution can become a Creditor. Creditors in bankruptcy itself are divided into 3 (three) levels. The problem is how the position of the state as the holder of PNBP itself in the bankruptcy process and how it is implied in one of the Commercial Court decisions, namely Decision Number 18/Pdt.Sus-Renvoi/2023/PN Niaga Medan. The results of the study show that, based on positive law in Indonesia, the position of the State as a holder of non-tax revenues in the bankruptcy process is as a Preferred Creditor. Furthermore, the consideration of the panel of judges in Decision Number 18/Pdt.Sus-Renvoi/2023/PN Niaga Medan can be said to be less precise in accommodating the position of the State itself.